Tratamento terminográfico de termos em inglês do comércio Internacional em dicionários franceses - Barros, Lidia Almeida [UNESP]; Silva, Francine Ferraz da (My University, 2010)
Brazil has a strong trading relationship with several countries, including France, which has intensified these links in recent years and intends to do so yet further. Legal documents regulate this operation, resulting in a set of terms which designate concepts specific to this area. Communication between Brazilian and French buyers and sellers is intense and does not permit the occurrence of errors in understanding orders for merchandise nor in terms of purchase and sale. It is therefore very important that agents of International Trade between Brazil and France should have access to a specialised terminographic tool in the area, containing the relevant terms used in French and Portuguese. This type of work does not currently exist; we therefore decided to make a contribution and draw up a proposal for a bilingual French-Portuguese dictionary in this specialised area. During our research, we registered a significant presence of English terms in International Trade texts originally written in Portuguese and in French, which may be explained by the fact that English currently has the role of global lingua franca. However, it is well known that France operates a policy of linguistic protectionism, making the use of French obligatory in all sectors of activity in France. This generated an area of doubt: how should one deal with English terms in a bilingual French-Portugese dictionary? In order to begin the search for an answer to this question, we decided to see what treatment was given to English terms in the area of International Trade in some French dictionaries. In this paper we shall present the principal results obtained during our research.

O Brasil mantém forte relação comercial com diversos países, dentre eles a França, que, aliás, tem intensificado essa relação nos últimos anos e pretende alimentá-la ainda mais. Documentos legais regulamentam essa operação, gerando um conjunto de termos que designam conceitos próprios dessa área. A comunicação entre vendedores e compradores brasileiros e franceses é intensa e não podem ocorrer erros na compreensão das solicitações de mercadorias e nas condições de compra e venda. Nesse sentido, é importante que os agentes do Comércio Internacional entre Brasil e França disponham de um instrumento terminográfico especializado na área que contenha os termos empregados nesse domínio em francês e em português. Esse tipo de obra não existe hoje; decidimos, então, dar uma contribuição e elaborar uma proposta de dicionário bilíngue francêsportuguês dessa área de especialidade. Durante nossa pesquisa, constatamos uma forte presença de termos em inglês em textos de Comércio Internacional originalmente escritos em português e em francês, o que se explica pelo fato de o inglês exercer, na atualidade, o papel de língua franca entre os povos. Sabemos, no entanto, que a França adota uma política de protecionismo linguístico, obrigando o uso do francês em todos os setores de atividade da França. Surgiu-nos, então, o questionamento: como tratar os termos em inglês em um dicionário bilíngue francês-português? Para iniciar o percurso de resposta a essa pergunta, decidimos verificar o tratamento dado aos termos em inglês do domínio do Comércio Internacional em alguns dicionários franceses. Nesta comunicação, apresentaremos os principais resultados obtidos em nossa pesquisa.
Keywords: terminologia; terminografia; comércio internacional; estrangeirismos; terminology; terminography; international trade; foreign terms